Green synthesis of ZnO nanoparticles using polyphenol extracts from pepper waste (Capsicum annuum) - Jiménez Rosado, Mercedes (2022)
The nanoparticles (NPs) synthesis poses an environmental problem: the formation of other toxic substances. An eco-friendlier alternative method based on the use of polyphenolic extracts is gaining interest due to their potential to reduce metal salts for the formation of NPs without toxic products. Thus, the main objective of this work was to obtain zinc oxide (ZnO) NPs from pepper extracts rich in polyphenols. To this end, the polyphenol extraction process was set-up using a response surface analysis of the different parameters involved (i.e. temperature, extraction time, amount of pepper and solvent used, type of solvent and part of the pepper used -whole fruit, pulp or waste-) in terms of total polyphenol content (TPC) and antioxidant activity of the extracts. The optimal extracts were used to synthesize ZnO NPs by colloidal precipitation, which were further characterized through X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy and antioxidant activity tests. In addition, the green NPs were compared with those obtained from chemical reagents. The green synthesized NPs were purer (100 and 88% ZnO content for green and chemical NPs) and smaller (24–43 and 35–70 nm for green and chemical NPs). The results show the great potential of pepper polyphenol extracts to obtain ZnO NPs by a green synthesis, being a great contribution to environmental sustainability.